2021
DOI: 10.3390/nu13124397
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Mitigate Chemotherapy and Radiation Toxicities That Affect Eating

Abstract: Background: Cancer and its therapy is commonly associated with a variety of side effects that impact eating behaviors that reduce nutritional intake. This review will outline potential causes of chemotherapy and radiation damage as well as approaches for the amelioration of the side effects of cancer during therapy. Methods: Information for clinicians, patients, and their caregivers about toxicity mitigation including nausea reduction, damage to epithelial structures such as skin and mucosa, organ toxicity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 168 publications
(254 reference statements)
0
12
0
Order By: Relevance
“…ifosfamide, ifosfamide with or without etoposide is often the 2 nd line therapy of choice (31-34). When ifosfamide is given with mesna as a continuous infusion, thrombocytopenia, encephalopathy, and renal toxicity are seen less often (33)(34)(35)(36)(37)63). We have also demonstrated that outpatient continuous infusion of ifosfamide + mesna was associated with fewer transfusions and episodes of fever and neutropenia (63).…”
Section: Other Chemotherapy Agents Worth Determining Suitability In C...mentioning
confidence: 66%
See 2 more Smart Citations
“…ifosfamide, ifosfamide with or without etoposide is often the 2 nd line therapy of choice (31-34). When ifosfamide is given with mesna as a continuous infusion, thrombocytopenia, encephalopathy, and renal toxicity are seen less often (33)(34)(35)(36)(37)63). We have also demonstrated that outpatient continuous infusion of ifosfamide + mesna was associated with fewer transfusions and episodes of fever and neutropenia (63).…”
Section: Other Chemotherapy Agents Worth Determining Suitability In C...mentioning
confidence: 66%
“…Tyrosine kinase inhibitors including regorafenib ( 2 , 64 ) and cabozantinib ( 3 ) have efficacy against osteosarcoma. Although a dose adjustment of TKI is sometimes needed to limit skin or GI toxicity, we have found the use of glutamine-disaccharide (Healios) can be helpful in ameliorating GI side effects and helping in eating and nutrition while on these agents ( 35 ).…”
Section: Alpha Emitter Radium-223 For Osteosarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of oral mucositis is approximately 20–40% in patients undergoing chemotherapy, 60–85% in patients receiving HSCT, and up to 90% in patients with head and neck cancer undergoing chemoradiotherapy [ 3 ]. Oral mucositis is a painful condition that can cause poor oral hygiene, difficulty eating and swallowing, altered nutritional intake, and decreased quality of life [ 4 , 5 ]. Severe oral mucositis can lead to a reduction or discontinuation of cancer treatment, resulting in a poor prognosis [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…lymphocyte counts as studied by Tang et al [13], intermittent fasting using 12-15 h instead of 48 h time periods may be more practical for a family-centered care approach [2]. Overall, the 13 papers included in this Special Issue highlight numerous state-of the art scientific contributions and the importance of diet and nutrition during chemotherapy and radiation.…”
mentioning
confidence: 99%